Visual Acuity, Full-field Stimulus Thresholds, and Electroretinography for 4 Years in The Rate of Progression of USH2A-related Retinal Degeneration (RUSH2A) Study - David G. Birch, PhD; Peiyao Cheng, PhD; Maureen G. Maguire, PhD; Jacque L. Duncan, MD; Allison R. Ayala, MS; Janet K. Cheetham, PharmD; Nicole R. Doucet, MPH; Todd A. Durham, PhD; Abigail T. Fahim, MD, PhD; Frederick L. Ferris, III, MD; Rachel M. Huckfeldt, MD, PhD; Michele Melia, ScM; et al. (Ophthalmology Science)
Purpose: To describe progression of best-corrected visual acuity (BCVA), full-field stimulus thresholds (FST), and electroretinography (ERG) over 4 years in the USH2A-related Retinal Degeneration study and to assess their suitability as clinical trial endpoints. Design: Prospective natural history study. Participants: Participants (n = 105) with biallelic disease-causing sequence variants in USH2A and BCVA letter scores of ≥54 were included. Methods: BCVA, FST, fundus-guided microperimetry, static perimetry, and spectral domain OCT were performed annually and ERG at baseline and 4 years only. Mixed effects models were used to estimate annual rates of change with 95% confidence intervals. Associations of change from baseline to 4 years between BCVA, FST, ERG, and other metrics were assessed with Spearman correlation coefficients (rs). Main Outcome Measures: Best-corrected visual acuity, FST, and ERG. Results: The annual rate of decline in BCVA was 0.83 (95% confidence interval: 0.65−1.02) letters/year. For FST, the change was 0.09 (0.07−0.11) log cd.s/m2/year for white threshold, 0.10 (0.08−0.12) log cd.s/m2/year for blue threshold, and 0.05 (0.04−0.06) log cd.s/m2/year for red threshold. Changes were 22.6 (17.4−28.2)%/year for white threshold, 26.0 (20.3−32.1)%/year for blue threshold, and 12.3 (8.7−16.0)%/year for red threshold. The high percentage of eyes with undetectable ERGs at baseline limited assessment of change. Conclusions: Best-corrected visual acuity was not a sensitive measure of progression over 4 years. Full-field stimulus threshold was a more sensitive measure; however, additional information on the clinical relevance of changes in FST is needed before this test can be adopted as an endpoint for clinical trials. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.